Frequencies of CYP1A2 Single Nucleotide Polymorphism in Indonesian and Its Effect on Blood Pressure - Erizal Sugiono; Andi Wijaya; Anwar Santoso; Ferry Sandra; Ilham Jaya Patellongi; Irawan Yusuf (The Indonesian Biomedical Journal, 2018)
BACKGROUND:  The association between caffeine with blood pressure (BP) still remains controversial. Caffeine is mainly metabolized by cytochrome-P450 (CYP)1A2 enzyme. Polymorphism of CYP1A2 is known to cause interindividual variation on enzymatic activity, thus affects caffeine metabolism and its effect on cardiovascular (CV) system.METHODS: We conducted a cross-sectional study and recruited 121 Indonesian subjects aged 25-60 years with varying coffee-drinking habits. DNA was extracted from peripheral blood and genotyped by polymerase chain reaction-restriction fragment length polymorphism (PCRRFLP) technique. Blood pressures were measured in the morning prior to the daily activity. Caffeine concentration in blood plasma was measured using high-performance liquid chromatography (HPLC). The differences between variables were analyzed using MannWhitney analysis and the correlations among variables were determined using multivariate logistic regression analysis.RESULTS: This study showed that the frequencies of single nucleotide polymorphisms (SNPs) among Indonesian were 31.8%, 18.2%, 25.2% and 24.8% respectively for CYP1A2*1A, CYP1A2*1B, CYP1A2*1C and CYP1A2*1F alleles. The genotype analysis showed that the subject number of the wild type (*1A/*1A) and the variants were 9.92% and 90.08%. There were no significant differences in term of BP levels among CYP1A2 genotypes and coffee drinking habit groups.CONCLUSIONS: The frequencies of CYP1A2 SNPs in Indonesian are different with frequencies in other populations. Since the association were not statistically significant, CYP1A2 polymorphisms as the predictor of elevated blood pressuare should be investigated further.KEYWORDS: coffee, caffeine, blood pressure, single nucleotide polymorphism, CYP1A2